Injecting and Sexual Networks and Sociodemographic Factors and Dual HIV Risk among People Who Inject Drugs: A Cross-sectional Study in Kermanshah Province, Iran - Noroozi, Mehdi (Addict Health, 2016)
BACKGROUND: Few studies suggest that social network factors, including size of sexual network may associate with drug-related and sexual high-risk behaviors. The objective of this study is to investigate injecting and sexual networks and sociodemographic factors that might be associated with dual HIV risk (DHR) among people who inject drug (PWID). METHODS: The data from a cross-sectional study of 455 PWID that were recruited through peer-referral sampling were used in this study. The data were collected using a structured questionnaire consisted of modules on sociodemographic characteristics, sexual and injection-related risk behaviors during 12 months before the interview. DHR was defined as engaged in both using a syringe previously used by other PWIDs and unprotected sex during last 12 months. Data analysis was performed with descriptive and logistic regression. In final model, we considered variables with P < 0.500 as statistically significant. Finally, reported adjusted odds ratio (AOR) and confidence interval (95% CI) for variables that were significant in the final model. FINDINGS: A total of 455 men who injected drugs participated in this study. The mean age ± standard deviation (SD) was 33.2 ± 7.3 (range 19-58) years. Overall, the prevalence of DHR In the last 12 months, 38% (95% CI: 18.3-51.2%). Multivariate model showed that regular visit to needle, syringe programs (NSPs) reduced odd of HDR to 50% when adjusted for other covariates, but still remained statistically significant (P < 0.050). The odds of reporting DHR was significantly higher in those ≥ 2 sex partners and injection partner (P < 0.010). Odds of DHR was higher (AOR: 2.3) among participants who had more than 2 injection per day but was not statistically significant (P > 0.050). CONCLUSION: DHR was common in PWID in Kermanshah, Iran. Having multiple injecting and sexual partners increased the odds of engaging in dual risk behaviors, but regular visit of NSPs can reduce the DHR among PWID.